Analisis Pengendalian Kualitas Di Mesin Spot Welding Manual Departemen Welding Dengan Metode Quality Control Circle (QCC) pada PT. XYZ - Shafter Rizqi Majid; Wahyudin Wahyudin; Dene Herwanto (Jurnal Ilmiah Wahana Pendidikan, 2022)
Abstract: Quality control is important so that companies can remain competitive in an increasingly tight industrial era. The purpose of this study was to control the quality of production failures that occurred at PT. XYZ especially the welding process. This type of research is applied research by applying the Quality Control Circle (QCC) method in controlling the quality of PT. XYZ. The data used in this study is the number of defects in production in the welding department. From the results obtained, the type of non-center spot defect is the most dominant type of defect with 37.4%. It is known that the cause of the out-of-center spot is dominated by an unstable engine factor. From the improvements that have been made, it is known that it can reduce the number of defects according to the target, namely 95% and can save costs of Rp. 3,508.866. Keyword: Quality, Defect, QCC.